2012 IEEE Fifth International Conference on Cloud Computing 2012
DOI: 10.1109/cloud.2012.74
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Taxonomy of Performance Evaluation of Commercial Cloud Services

Abstract: Cloud Computing, as one of the most promising computing paradigms, has become increasingly accepted in industry. Numerous commercial providers have started to supply public Cloud services, and corresponding performance evaluation is then inevitably required for Cloud provider selection or cost-benefit analysis. Unfortunately, inaccurate and confusing evaluation implementations can be often seen in the context of commercial Cloud Computing, which could severely interfere and spoil evaluation-related comprehensi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 20 publications
1
44
0
5
Order By: Relevance
“…Distinctly the selection of an appropriate framework depend on provision of its features that could be evaluated through fundamental metrics [30]. In this section, we have presented the fundamental aspects and their perspective QoS metrics through that the services (which provide QoS for multimedia applications over cloud computing) could be evaluated.…”
Section: Qos Metrics For Cloudy Multimedia Evaluationmentioning
confidence: 99%
“…Distinctly the selection of an appropriate framework depend on provision of its features that could be evaluated through fundamental metrics [30]. In this section, we have presented the fundamental aspects and their perspective QoS metrics through that the services (which provide QoS for multimedia applications over cloud computing) could be evaluated.…”
Section: Qos Metrics For Cloudy Multimedia Evaluationmentioning
confidence: 99%
“…4), we name the Scalability from the second perspective of changing workload as Original Scalability. Moreover, it has been identified that Cloud service variability and scalability have to be reflected by the change of value of other performance features [30]. Corresponding to the aforementioned MediaWise architecture, we may evaluate the variability and scalability of Cloud services through observing the performance change around three physical properties, namely Communication (e.g., Ethernet), Computation (e.g., VM Instance), and Storage (e.g., BLOB Original Scalability:…”
Section: Requirement Recognition and Service Feature Identificationmentioning
confidence: 99%
“…In this paper, we use variability to indicate the extent of fluctuation in values of an individual service performance index. Considering Cloud service variability could be related to time and location [30], we define two requirement questions around variability: How variable are the related Cloud services when running MediaWise Cloud for a period of time?…”
Section: Requirement Recognition and Service Feature Identificationmentioning
confidence: 99%
“…When it comes to the performance evaluation of Cloud services, our previous taxonomy work [15] can be used to facilitate exploring available performance properties. Following the original study, we directly identified the combination of the related performance properties as Computation Latency and also Variability of Computation Latency, as shown in Figure 2.…”
Section: ) Service Feature Identificationmentioning
confidence: 99%
“…By exploring the existing practices of Cloud services evaluation [19], we show that three service features have been mainly of concern, namely Performance, Economics, and Security. In particular, the elements of the Performance feature can be divided into Physical Properties and Capacities [15], while the Economics feature covers Cost and Elasticity of using Cloud services. Although the Security feature has not been well evaluated yet [19], it may comprise numerous security concerns ranging from access control to prosecution [4], [8].…”
Section: B Service Feature Identificationmentioning
confidence: 99%